2018
DOI: 10.31784/zvr.6.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Strukturne reforme zemalja CEE-a u tranzicijskom razdoblju

Abstract: Procesi financijske intermedijacije imali su važnu ulogu u transformaciji zemalja CEE-a u tržišne ekonomije. Intervencije države u mobiliziranju i alociranju financijskih resursa prepoznate su kao efikasan i brz put k razvijanju financijskih sustava. Stoga su nositelji ekonomske politike usmjerili svoje napore k osiguranju bazičnih zakonodavnih okvira i potrebne infrastrukture, kao i dizajniranju i implementiranju primjerenih strukturnih reformi. Uz navedeno, razvoj sustava potaknut je i adekvatnim institucijs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…But the aging of the population also causes a very big problem on the revenue side of the system no matter how funds are raised to finance it. However, it should be borne in mind that frequent changes imply an uncertain institutional environment which can have negative implications for growth (Buterin et al, 2017;Olgić Draženović et al, 2018). To assess the risk to the sustainability of public finances over the next few decades, most countries face the need to project future health spending and other components of the social security system.…”
Section: Health Care Consumptionmentioning
confidence: 99%
“…But the aging of the population also causes a very big problem on the revenue side of the system no matter how funds are raised to finance it. However, it should be borne in mind that frequent changes imply an uncertain institutional environment which can have negative implications for growth (Buterin et al, 2017;Olgić Draženović et al, 2018). To assess the risk to the sustainability of public finances over the next few decades, most countries face the need to project future health spending and other components of the social security system.…”
Section: Health Care Consumptionmentioning
confidence: 99%
“…This reform, based on three pillars, aimed at diversifying pension sources, increasing individual accountability for pensions and contributing to the long-term financial sustainability of the system (Puljiz, 2011). However, it should be noted that during the 2008 global recession, due to the fall in securities prices on the global financial markets, the viability of pension pain funds was called into question, which indicated that such a pension system had weaknesses (Olgić Draženović et al, 2018). In 2010, a gradual leveling of the conditions of age for women and men was adopted, an attempt was made to reward persons who became eligible for full retirement age and remain in the world of work, and discontinued early retirement.…”
Section: The Effectiveness Of the Reforms Implementedmentioning
confidence: 99%
“…Moreover, he believes that the partial measures will make the situation even worse and that future generations will find the system in an even more difficult state than it is today. On the other hand, frequent changes in the tax structure suggest a precarious institutional environment that is considered one of the main derivatives of the economic growth of national economies (Buterin et al, 2018). Chart 5 shows HZMO expenditures for pensions and retirement benefits.…”
Section: Chart 4 Share Of Average Net Pension In Average Wagementioning
confidence: 99%
“…Treba ipak imati na umu da premda postoje autori koji hrvatsko tržište vrijednosnih papira, odnosno Zagrebačku burzu smatraju modernim tržištem uređenim u skladu sa stečevinama Europske unije, ipak je ono nedovoljno razvijeno, odnosno usko zbog malog broja ulagača i plitko zbog malog broja naloga koji bi bili u stanju dovesti do značajnijih pomaka cijena i burzovnih indeksa te je posljedično nedovoljno likvidno i ne sasvim efikasno (Schabek et al, 2019;Olgić Draženović et al, 2016). Takva situacija očekivani je nastavak višedesetljetnog sustava krutog kreditno-distributivnog sustava financiranja uz veliku ulogu bankovnog aparata (Olgić Draženović et al, 2018). Iako rezultate provedene ex post tehničke analize promatranih poduzeća treba sagledavati u okviru trenutne situacije na Zagrebačkoj burzi, oni ipak daju odgovor na pitanje utjecaja sezonskih oscilacija na kretanje cijene.…”
unclassified